2020
DOI: 10.1177/1940082920906970
|View full text |Cite
|
Sign up to set email alerts
|

Response of Understory Bird Feeding Groups to Deforestation Gradient in a Tropical Rainforest of Cameroon

Abstract: Birds are crucial in maintaining the balance of many ecosystems and provide various ecological services. Understanding their sensitivity to human disturbances should be prioritized in understudy areas for effective conservation practices. Using mist nets, this study characterized mostly understory bird communities (insectivorous, frugivorous, granivorous, and nectarivorous birds) in three habitat types (pristine forest, selectively logged forest, and young oil palm plantation) in the Talangaye rainfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 48 publications
(51 reference statements)
2
22
0
Order By: Relevance
“…Birds are good indicators of habitat quality (Kupsch et al, 2019), with groups such as insectivores showing high sensitivity to habitat degradation (Karp et al, 2011;Powell et al, 2015;Stratford & Stouffer, 2013;Tchoumbou et al, 2020;Wolfe et al, 2015). In the tropics, many bird species depend strictly on microhabitats often only present in pristine forest (forest specialists; Stratford & Stouffer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Birds are good indicators of habitat quality (Kupsch et al, 2019), with groups such as insectivores showing high sensitivity to habitat degradation (Karp et al, 2011;Powell et al, 2015;Stratford & Stouffer, 2013;Tchoumbou et al, 2020;Wolfe et al, 2015). In the tropics, many bird species depend strictly on microhabitats often only present in pristine forest (forest specialists; Stratford & Stouffer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A study comparing a protected area with an agricultural area in Serengeti showed that at least 50% of insectivorous and granivorous birds found in forests were absent in agriculture, suggesting that more intact ecosystems can safeguard a large proportion of specialist species (O'Connell et al 2000;Sinclair et al 2002). In a similar study, bird functional diversity depended on the overall habitat types , and the intactness of forest, in which species responded negatively to disturbance gradient, for example, omnivores, insectivores and frugivores were lowest in numbers in areas with selective logging and plantation conversions within a tropical rainforest (Tchoumbou et al 2020). The intactness of KBAs strongly relies on the physical features (e.g., landscape structure), presence of threats, and changes in land-use (Rayner et al 2014).…”
Section: Body Mass (Kg)mentioning
confidence: 81%
“…Whereas land-use driven threats such as deforestation and agricultural expansion remain a key threat to 49% of species particularly those forestdwelling species with narrow distributions. In contrast with other threats, deforestation and agricultural expansions led to habitat fragmentation that may immediately influence the alterations of diversity and composition of native species present in these systems (Bujoczek et al 2020;Hatfield et al 2020;Tchoumbou et al 2020). Declining strict forest-dwelling species at a regional scale is widely associated with human disruption to habitats that reduce the space occupied by and affect the foraging grounds of a diverse set of species (Brooks et al 1999;Renjifo 2001).…”
Section: Body Mass (Kg)mentioning
confidence: 99%
See 1 more Smart Citation
“…2016) or selective logging and establishment of palm oil plantations can have variable effects on dietary guilds of bird communities (Tchombou et al . 2020a). Bregman et al .…”
Section: Logging Status and Prevalencementioning
confidence: 99%